2008
DOI: 10.1021/jp808104f
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Mechanical Investigation of the Influence of the Local Environment on the Vibrational Properties of Hydrogenated Si(111)

Abstract: Periodic density functional calculations were performed to investigate the vibrational properties of hydrogenated and grafted Si(111) surfaces as a function of surface coverage and subsurface oxidation. Surfaces terminated with -CH 3 , -CCH, and -Cl groups were considered. Subsurface oxidation was taken into account by oxidizing one, two, and three silicon back bonds. The effect of anharmonicity was considered in the calculation of the stretching frequencies of the Si-H and C-H groups. The effect of the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 50 publications
4
12
0
Order By: Relevance
“…The partial coverage can be detected by IR spectroscopy 41 because the local environment affects the SiH and SiCl stretching frequencies, as we showed in previous work. 42 Taking into account that SiH and SiCl surface groups have such different reactivities, the partial chlorination of the surface may be viewed as a tool to functionalize the surface selectively at the highly reactive SiCl surface sites.…”
Section: Reactionmentioning
confidence: 99%
“…The partial coverage can be detected by IR spectroscopy 41 because the local environment affects the SiH and SiCl stretching frequencies, as we showed in previous work. 42 Taking into account that SiH and SiCl surface groups have such different reactivities, the partial chlorination of the surface may be viewed as a tool to functionalize the surface selectively at the highly reactive SiCl surface sites.…”
Section: Reactionmentioning
confidence: 99%
“…After an exposure time of 3 min at a temperature of 95 °C, a 50% chlorine coverage is obtained . The chlorination can be monitored by the IR frequency shifts of the Si–H and Si–Cl stretching modes, as they are sensitive to the local environment. , …”
Section: Introductionmentioning
confidence: 99%
“…Hence, there is a need to conduct a study on the strain effect on oxidation kinetics. So far, basic aspects of the initial stages of oxidation of unstrained hydrogen-terminated Si(111) (H–Si(111)) surfaces have been elucidated. ,,, Estimation of the rate of the surface oxidation process, which is especially sensitive to oxygen incorporations, was done by using the Si–H stretching mode as a probe. , Chabal et al found that a non-integer order of 1.5 in the Si–H consumption rate is an indicator of a multistep mechanism of oxidation . In another study by Federico et al, they concluded that perfect hydrogenated Si(111) is unreactive toward H 2 O vapor and O 2 at room temperature according to density functional theory (DFT) .…”
Section: Introductionmentioning
confidence: 99%
“…So far, basic aspects of the initial stages of oxidation of unstrained hydrogen-terminated Si(111) (H−Si(111)) surfaces have been elucidated. 6,15,17,18 Estimation of the rate of the surface oxidation process, which is especially sensitive to oxygen incorporations, was done by using the Si−H stretching mode as a probe. 17,18 Chabal et al found that a non-integer order of 1.5 in the Si−H consumption rate is an indicator of a multistep mechanism of oxidation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation